A process for the preparation of a catalyst for the synthesis of aviation kerosene from synthesis gas, the catalyst thus obtained and its use
Patent Information
- Application Number
- CN202610935310.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2018-04-13
- Publication Date
- 2026-10-20
AI Technical Summary
合成气制航空煤油为强放热反应并有副产物水生成,钴基单金属催化剂因易氧化导致其在反应中易团聚、烧结、失活;普通费托反应符合ASF分布,目标产物(即航空煤油)选择性低,理论值不超过40%。本发明中,通过先用弱酸和强碱对载体进行热处理,然后再负载催化活性组分(Ru、Fe、Ni、Co、Pt、Pd或其任意组合)和催化助剂,可获得高分散性的合成气制航空煤油用催化剂,有利于解决催化剂在反应过程中稳定性差的问题,提高催化剂的稳定性,并能打破传统费托反应的ASF分布,特别是能够获得航空煤油的高选择性,此外还可获得可接受的或更高的CO转化率。
Smart Images

Figure SMS_1
Abstract
Description
[0001] This application is a divisional application of patent application No. 201810331053.X, filed on April 13, 2018, entitled "A method for preparing a catalyst for synthesizing aviation kerosene from syngas and the catalyst obtained therefrom and its application". Technical Field
[0002] This invention relates to a method for preparing a catalyst for synthesizing aviation kerosene from syngas, and also to the catalyst obtained by the method and its application. Background Technology
[0003] Aviation kerosene, also known as jet fuel, is primarily used as fuel for jet spacecraft engines. It is currently a liquid fuel with high international demand, typically composed of a mixture of hydrocarbons with 8-16 carbon atoms. Due to the ever-increasing demand for aviation kerosene, its price remains high, making its synthesis a focus of global attention. It is estimated that by 2020, my country's demand for aviation kerosene will exceed 40 million tons. Currently, aviation kerosene production mainly involves the following methods: 1) Distillation from crude oil. This method heavily relies on increasingly depleted petroleum resources and requires high-quality equipment; 2) High-temperature pyrolysis of biomass to produce biomass oil, which is then deoxygenated and upgraded into liquid fuel. This process is complex, and the resulting biomass oil is of poor quality and cannot be directly used as engine fuel, requiring further refining; 3) Biomass undergoes chemical and biological treatment (including hydrolysis, fermentation, selective hydrogenation, etc.) to obtain small-molecule compounds, which are then used as raw materials to obtain aviation kerosene with a chain length (C8-C10). 16Syngas is an oxygen-containing organic compound. The process is complex, technologically immature, and requires excessive investment. Syngas, as a bridge for energy conversion, can transform coal, natural gas, and biomass into clean oil products, and is considered one of the most promising alternatives to petroleum. In the 1920s, Fischer and Tropsch developed a synthetic route for synthesizing hydrocarbons (liquid fuels) from syngas under catalytic conditions, known as the Fischer-Tropsch synthesis. This route first produces syngas from non-petroleum resources, then catalytically hydrogenates CO to produce liquid fuels. This C1 synthesis route not only has the advantages of being green and environmentally friendly, with mild reaction conditions and high atom economy, but also has significant strategic importance for adjusting the world's energy structure and reducing dependence on petroleum resources. However, the traditional Fischer-Tropsch synthesis product distribution follows the Anderson-Schulz-Flory (ASF) distribution, meaning that the theoretical selectivity for aviation kerosene in the ASF distribution is less than 40%, hindering the industrial production of aviation kerosene via the Fischer-Tropsch reaction. It is evident that breaking the traditional ASF distribution of the Fischer-Tropsch reaction is key to realizing the industrial production of aviation kerosene from syngas. Among these, the development of catalysts in the syngas-to-aviation kerosene reaction is crucial to breaking the traditional ASF distribution of the Fischer-Tropsch reaction.
[0004] Studies have shown that the direct production of aviation kerosene from syngas requires breaking the traditional ASF distribution and concentrating the products in the C8-C range. 16 For example, Toyama University used the method of injecting olefins into the reactor to shift the ASF distribution curve towards the aviation kerosene distribution range (J. Li, G. Yang, Y. Yoneyama, T. Vitidsant, N. Tsubaki, Fuel, 2016, 171:159-166) to improve the selectivity of aviation kerosene. However, this method requires an additional olefin injection process and is not suitable for fixed-bed reactors, thus having low applicability.
[0005] As is well known, the synthesis of aviation kerosene from syngas is a strongly exothermic reaction that produces water as a byproduct. Cobalt-based monometallic catalysts are prone to oxidation, leading to agglomeration, sintering, and deactivation during the reaction. The conventional Fischer-Tropsch reaction conforms to the ASF distribution and has low selectivity for the target product, which limits the large-scale application of this route in the synthesis of aviation kerosene. Summary of the Invention
[0006] In view of the aforementioned state of the prior art, the inventors of this invention have conducted extensive and in-depth research on catalysts for syngas-to-aviation kerosene production, aiming to discover a new method for preparing such catalysts. Catalysts prepared by this method, when used in syngas-to-aviation kerosene production, can break the traditional ASF distribution of the Fischer-Tropsch reaction, achieving high selectivity for aviation kerosene production, and further achieving acceptable or higher CO conversion rates. The inventors have discovered that, in preparing the catalyst for syngas-to-aviation kerosene production, if the support is first heat-treated with a weak acid and a strong base before loading a catalyst promoter and a catalytically active metal, the catalyst prepared in this way, when used in syngas-to-aviation kerosene production, can break the traditional ASF distribution of the Fischer-Tropsch reaction, achieving high selectivity for aviation kerosene production, and further achieving acceptable or higher CO conversion rates. This invention is based on the aforementioned findings.
[0007] Therefore, one object of the present invention is to provide a method for preparing a catalyst for syngas-to-aviation kerosene. This method involves first heat-treating a support with a weak acid and a strong base, and then loading a catalyst promoter and a catalytically active metal. The catalyst prepared in this way, when used in the syngas-to-aviation kerosene production process, can break the traditional ASF distribution of the Fischer-Tropsch reaction, achieving high selectivity for aviation kerosene, and further achieving acceptable or higher CO conversion rates.
[0008] Another object of the present invention is to provide a catalyst for producing aviation kerosene from syngas prepared by the method of the present invention. When used in the production of aviation kerosene from syngas, this catalyst can break the ASF distribution of the conventional Fischer-Tropsch reaction, achieving high selectivity for aviation kerosene, and further achieving acceptable or higher CO conversion rates.
[0009] A final object of the present invention is to provide the use of the catalyst prepared by the method of the present invention as a catalyst in the production of aviation kerosene from syngas. When used in the production of aviation kerosene from syngas, this catalyst can break the ASF distribution of the conventional Fischer-Tropsch reaction, achieving high selectivity for aviation kerosene, and further achieving acceptable or higher CO conversion rates.
[0010] The technical solution for achieving the above-mentioned objectives of this invention can be summarized as follows: 1. A method for preparing a catalyst for producing aviation kerosene from syngas, the catalyst being a supported catalyst comprising a support and a catalytically active component and a catalytic promoter supported on the support, the catalyst comprising, based on its total weight: (A) One or more elements selected from Ru, Fe, Ni, Co, Pt and Pd, in an elemental composition of 1-50% by weight, are used as the catalytically active component. (B) One or more elements selected from Group I metals, transition elements, and lanthanides of the periodic table, differing from the catalytically active component, and expressed as 1-20% by weight, as a catalytic promoter; (C) Carrier, The catalyst is characterized by being prepared by a method comprising the following steps: (1) The carrier is ionized using the constant K a 1.0×10 -3 -1.0×10 -1 Heat treatment of weak acid aqueous solution; (2) The carrier obtained in step (1) is heat-treated with an aqueous solution of alkali metal hydroxide under alkaline conditions; (3) The product obtained in step (2) is directly contacted with an aqueous solution of a water-soluble salt of a metal element as a catalyst, or the product obtained in step (2) is filtered, washed, and dried and then contacted with an aqueous solution of a water-soluble salt of a metal element as a catalyst to load the metal element as a catalyst. (4) The product obtained in step (3) is filtered, washed, dried, and calcined, and then contacted with the water-soluble metal salt of the metal element as the catalytic active component or its solution to load the metal element as the catalytic active component; and (5) The product obtained in step (4) is calcined to obtain the catalyst.
[0011] 2. The method according to item 1, wherein the catalyst comprises, based on its total weight: (A) 5-30% by weight, more preferably 12-18% by weight, of the catalytically active component, and (B) 1-15% by weight, more preferably 8-12% by weight, of a catalyst promoter; and (C) 60-94% by weight, more preferably 70-80% by weight of the carrier.
[0012] 3. According to the method of paragraph 1 or 2, wherein the catalytically active component is one or more elements selected from Ni, Co and Fe, especially Co, Fe or combinations thereof; and / or the catalyst promoter is one or more elements selected from Na, K, La, Ce and Mn, especially La, Ce or combinations thereof; and / or the support is one or more elements selected from carbon nanotubes, graphene, activated carbon, SiO2, Al2O3, ZrO2, silicon carbide, TiO2 and molecular sieves, preferably one or more molecular sieves, especially Y-type molecular sieves, clinoptilolite, mordenite and ZSM-5, provided that: when the catalyst promoter is Ti, the support is not TiO2, and when the catalyst promoter is Zr, the support is not ZrO2.
[0013] 4. The method according to any one of items 1-3, wherein the water-soluble metal salt of the catalytic active component is a nitrate, acetate, chloride salt, their hydrates or any mixture thereof, preferably a nitrate or its hydrate; and / or, the water-soluble salt of the catalytic promoter is a nitrate, acetate, chloride salt, their hydrates or any mixture thereof, preferably a nitrate or its hydrate.
[0014] 5. The method according to any one of items 1-4, wherein the weak acid in step (1) is an organic weak acid, preferably selected from one or more of oxalic acid, phenylhexacarboxylic acid, maleic acid, salicylic acid and EDTA, especially EDTA; and / or the concentration of the aqueous solution of the weak acid in step (1) is 0.04-0.5 mol / L, preferably 0.04-0.1 mol / L; and / or the heat treatment in step (1) is carried out under conditions not exceeding the reflux temperature, preferably at 40-100°C. o C. More preferably 70-100 o The process is carried out at a temperature of C; and / or the heat treatment in step (1) is carried out for 1-10 hours, preferably 4-10 hours.
[0015] 6. The method according to any one of items 1-5, wherein the alkali metal hydroxide in step (2) is sodium hydroxide, potassium hydroxide, or a combination thereof, preferably sodium hydroxide; and / or, the concentration of the aqueous solution of the alkali metal hydroxide is 0.1-1 mol / L, preferably 0.1-0.5 mol / L; and / or, the heat treatment in step (2) is at 40-100°C. o C. Preferred 40-80 o The heat treatment is carried out at C; and / or the heat treatment time in step (2) is 0.1-2h, preferably 0.1-1h.
[0016] 7. The method according to any one of items 1-6, wherein the carrier obtained by step (1) is filtered, washed and dried before the heat treatment in step (2); and / or, in step (3), the product obtained in step (2) is filtered, washed and dried and then contacted with an aqueous solution of a water-soluble salt of a metal element as a catalyst to load the metal element as a catalyst.
[0017] 8. The method according to any one of items 1-7, wherein in step (3), the concentration of the aqueous solution of the water-soluble salt of the metal element as a catalyst promoter is 0.1-4 mol / L, preferably 0.5-2 mol / L; and in step (3), the contact between the support and the aqueous solution of the water-soluble salt of the metal element as a catalyst promoter is 40-100 °C. o C, preferably 40-80 oThe process is carried out at C; and / or the contact between the support and an aqueous solution of a water-soluble salt of a metal element serving as a catalyst is carried out for 2-24 hours, preferably 4-12 hours.
[0018] 9. The method according to any one of items 1-8, wherein in step (4), the water-soluble metal salt of the metal element as the catalytic active component is contacted in a molten state with the product obtained in step (3), preferably, the water-soluble metal salt of the metal element as the catalytic active component is mixed with the product obtained in step (3) and then melted in a sealed container.
[0019] 10. The method according to any one of items 1-9, wherein the drying in steps (2), (3) and (4) is each independently carried out at 60-120°C. o The roasting is carried out under C conditions; and / or, the roasting in steps (4) and (5) is carried out independently at 350-650 °C. o The roasting is carried out at C, preferably at 450-650 °C in step (4). o The roasting in step (5) is carried out at 350-500℃.
[0020] 11. A catalyst prepared by any one of the methods in items 1-10.
[0021] 12. Use of a catalyst prepared by any one of the methods in items 1-10 in the production of aviation kerosene from syngas.
[0022] 13. According to the use of item 12, wherein in the reaction of producing aviation kerosene from syngas, the H2 / CO molar ratio is 1-5, preferably 1-3, more preferably 1 to less than 2.
[0023] 14. According to the application in item 12 or 13, wherein in the reaction for producing aviation kerosene from syngas, the reaction pressure is 1-5 MPa (gauge pressure) and the reaction temperature is 150-350 °C. o C, and W / F are 5-20 gh mol -1 The preferred reaction pressure is 1-3 MPa (gauge pressure), and the preferred reaction temperature is 200-300 °C. o C and W / F are 8-15 gh mol -1 .
[0024] These and other objects, features and advantages of the present invention will be readily apparent to those skilled in the art upon consideration of the invention in conjunction with the following description. Detailed Implementation
[0025] According to one aspect of the present invention, a method for preparing a catalyst for producing aviation kerosene from syngas is provided. The catalyst is a supported catalyst comprising a support and a catalytically active component and a catalytic promoter supported on the support. Based on the total weight of the catalyst, the catalyst comprises: (A) One or more elements selected from Ru, Fe, Ni, Co, Pt and Pd, in an elemental composition of 1-50% by weight, are used as the catalytically active component. (B) One or more elements selected from Group I metals, transition elements, and lanthanides of the periodic table, differing from the catalytically active component, and expressed as 1-20% by weight, as a catalytic promoter; (C) Carrier, The catalyst is characterized by being prepared by a method comprising the following steps: (1) The carrier is ionized using the constant K a 1.0×10 -3 -1.0×10 -1 Heat treatment of weak acid aqueous solution; (2) The carrier obtained in step (1) is heat-treated with an aqueous solution of alkali metal hydroxide under alkaline conditions; (3) The product obtained in step (2) is directly contacted with an aqueous solution of a water-soluble salt of a metal element as a catalyst, or the product obtained in step (2) is filtered, washed, and dried before being contacted with an aqueous solution of a water-soluble salt of a metal element as a catalyst, so as to load the metal element as a catalyst. (4) The product obtained in step (3) is filtered, washed, dried, and calcined, and then contacted with the water-soluble metal salt of the metal element as the catalytic active component or its solution to load the metal element as the catalytic active component; and (5) The product obtained in step (4) is calcined to obtain the catalyst.
[0026] The catalyst of this invention is a supported catalyst, comprising a catalytically active component, a catalytic promoter, and a support, wherein the catalytically active component and the catalytic promoter are supported on the support. As the catalytically active component, it is typically one or more elements selected from Ru, Fe, Ni, Co, Pt, and Pd, preferably one or more elements selected from Co, Ni, and Fe, especially Co and / or Fe. The catalytically active component can exist in the catalyst as an element, as a compound such as an oxide, or as a mixture of both. Based on elemental composition, the catalyst of this invention typically contains 1-50% by weight of the catalytically active component, preferably 5-30% by weight, more preferably 12-18% by weight, based on the total weight of the catalyst.
[0027] The catalyst of this invention also includes a catalytic promoter. The presence of the catalytic promoter can further improve the selectivity of aviation kerosene in the production of aviation kerosene from syngas, and sometimes can also improve the CO conversion rate. As a catalytic promoter, it is usually one or more elements selected from Group I metals, transition elements, and lanthanides of the periodic table, which are different from the catalytically active component. Group I metals include Li, Na, and K. When Group I elements are used as catalytic promoters, Na and / or K are preferred. Transition elements refer to a series of metal elements in the d-block of the periodic table, which includes elements from groups 3 to 12, but does not include the inner transition elements in the f-block, that is, it does not include lanthanides and actinides. Transition elements mentioned include Sc, Y, Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Mn, Tc, Re, Os, Rh, Ir, Zn, Cd, and Hg. When transition metals are used as catalytic promoters, one or more selected from Mo, Mn, and Zn are preferred, with Mo and / or Mn being particularly preferred. Lanthanide elements include La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu. When lanthanides are used as catalyst promoters, one or more selected from La, Ce, Pr, and Tb are preferred, with La and / or Ce being particularly preferred. In a preferred embodiment of the invention, the catalyst promoter is one or more elements selected from Na, K, La, Ce, and Mn, especially La, Ce, or combinations thereof. The catalyst promoter can exist in the catalyst as an element, as a compound such as an oxide, or as a mixture of both. The catalyst of the present invention typically contains 1-20% by weight of the catalyst promoter, preferably 1-15% by weight, more preferably 8-12% by weight, based on the total weight of the catalyst.
[0028] The catalyst of this invention is a supported catalyst, in which the catalytically active component and the catalytic promoter are supported on a support. The support can be any support suitable for the catalytic synthesis of aviation kerosene from syngas. Preferably, the support is one or more supports selected from carbon nanotubes, graphene, activated carbon, SiO2, Al2O3, ZrO2, SiC, and molecular sieves; more preferably, it is one or more molecular sieve supports, especially one or more supports selected from Y-type molecular sieves, clinoptilolite, mordenite, and ZSM-5, provided that: when the catalytic promoter is Ti, the support is not TiO2; and when the catalytic promoter is Zr, the support is not ZrO2. The catalyst of this invention typically contains 40-98% by weight of support, preferably 60-94% by weight, more preferably 70-80% by weight of support, based on the total weight of the catalyst.
[0029] The catalyst of this invention is prepared by first heat-treating the support with a weak acid and a strong base, and then loading a catalytic promoter and a catalytically active metal. When used in the synthesis of aviation kerosene from syngas, this catalyst breaks the traditional ASF distribution of the Fischer-Tropsch reaction, achieving high selectivity for aviation kerosene. Furthermore, it can also achieve acceptable or higher CO conversion rates. Therefore, the catalyst of this invention is typically prepared by a method including the following steps: (1) The carrier is ionized using the constant K a 1.0×10 -3 -1.0×10 -1 Heat treatment of weak acid aqueous solution; (2) The carrier obtained in step (1) is heat-treated with an aqueous solution of alkali metal hydroxide under alkaline conditions; (3) The product obtained in step (2) is directly contacted with an aqueous solution of a water-soluble salt of a metal element as a catalyst, or the product obtained in step (2) is filtered, washed, and dried before being contacted with an aqueous solution of a water-soluble salt of a metal element as a catalyst, so as to load the metal element as a catalyst. (4) The product obtained in step (3) is filtered, washed, dried, and calcined, and then contacted with the water-soluble metal salt of the metal element as the catalytic active component or its solution to load the metal element as the catalytic active component; and (5) The product obtained in step (4) is calcined to obtain the catalyst.
[0030] First, in step (1), the ionization constant K needs to be used. a (At 25℃, when a weak electrolyte reaches ionization equilibrium in solution, the ratio of the product of the concentrations of all ions in the solution to the concentration of unionized molecules in the solution) is 1.0 × 10⁻⁶. -3 -1.0×10 -1 The support is heat-treated with a weak acid aqueous solution. Organic weak acids are advantageously used as the weak acid, particularly one or more selected from oxalic acid, phenylhexacarboxylic acid, maleic acid, salicylic acid, and EDTA (ethylenediaminetetraacetic acid), especially EDTA. In this heat treatment, the concentration of the weak acid aqueous solution is typically 0.04-0.5 mol / L, preferably 0.04-0.1 mol / L. This heat treatment is generally required to be carried out at a temperature above room temperature or at an elevated temperature. However, this temperature typically does not exceed the reflux temperature, for example, a heat treatment temperature of 40-100°C. o C, preferably 70-100 o C. The heat treatment time is usually 1-10 hours, preferably 4-10 hours.
[0031] After the heat treatment in step (1) is completed, the carrier obtained in step (1) can be directly heat-treated with an aqueous solution of alkali metal hydroxide under alkaline conditions, or the carrier obtained in step (1) can be filtered, washed, and dried before being heat-treated with an aqueous solution of alkali metal hydroxide under alkaline conditions, the latter being preferred. Here, "directly" means that the product obtained in step (1) does not require separation (e.g., without any step selected from filtration, washing, and drying) and is heat-treated with an aqueous solution of alkali metal hydroxide under alkaline conditions. For washing, deionized water or the like can be used, and washing can be performed once or multiple times. Advantageously, washing is carried out under reduced pressure, for example, under vacuum filtration conditions. For drying, the washed solid is typically dried at 60-120°C. o Dry at a temperature of C for 10-48 hours, preferably 10-24 hours.
[0032] In step (2), the carrier obtained in step (1) is heat-treated with an aqueous solution of an alkali metal hydroxide under alkaline conditions. Sodium hydroxide, potassium hydroxide, or a combination thereof can typically be used as the alkali metal hydroxide, with sodium hydroxide being preferred. The concentration of the aqueous solution of the alkali metal hydroxide is typically 0.1-1 mol / L, preferably 0.1-0.5 mol / L. This heat treatment can typically be performed at 40-100 °C. o C. Preferred 40-80 o The heat treatment is carried out at C. The duration of this heat treatment is typically 0.1-2 hours, preferably 0.1-1 hours.
[0033] In step (3), the product obtained in step (2) is directly contacted with an aqueous solution of a water-soluble salt of a metal element serving as a catalyst promoter, or the product obtained in step (2) is filtered, washed, and dried before being contacted with an aqueous solution of a water-soluble salt of a metal element serving as a catalyst promoter, so as to load the metal element serving as a catalyst promoter. Here, "directly" means that the product obtained in step (2) is contacted with an aqueous solution of a water-soluble salt of a metal element serving as a catalyst promoter without separation (e.g., without any step selected from filtration, washing, and drying). For washing, deionized water or the like can be used, and washing can be performed once or multiple times. Advantageously, washing is carried out under reduced pressure, for example, under vacuum filtration conditions. For drying, the washed solid is typically dried at 60-120 °C. oDrying at a temperature of C for 10-48 h, preferably 10-24 h. In step (3), an aqueous solution of a water-soluble metal salt of the metal as a catalyst is provided in water, preferably deionized water. The concentration of this aqueous solution of the water-soluble metal salt is typically 0.1-4 mol / L, preferably 0.5-2 mol / L. The water-soluble metal salt of the catalyst can be a nitrate, acetate, chloride salt, their hydrates or any mixture thereof, preferably a nitrate, acetate, their hydrates or any mixture thereof, especially a nitrate or its hydrate. In step (3), the contact between the treated support and the aqueous solution of the water-soluble salt of the metal element as a catalyst is typically 40-100 °C. o C, preferably 40-80 o The contact time is typically 2-24 hours, preferably 4-12 hours.
[0034] In step (4), the product obtained in step (3) is filtered, washed, dried, and calcined, and then contacted with the water-soluble metal salt of the metal element as the catalytic active component, or its solution, to load the metal element as the catalytic active component. For washing, deionized water or similar materials can be used; washing can be performed once or multiple times. Advantageously, washing is carried out under reduced pressure, for example, by vacuum filtration. For drying, the washed solid is typically dried at 60-120°C. o Dry at a temperature of C for 10-48 hours, preferably 10-24 hours. For calcination, the calcination temperature is typically 350-650°C. o C, preferably 450-650 oC. The calcination time is typically 2-8 hours, preferably 4-8 hours. The water-soluble metal salt of the metal element as the catalytically active component can be a nitrate, acetate, chloride salt, their hydrates, or any mixture thereof, preferably a nitrate, acetate, their hydrates, or any mixture thereof, especially a nitrate or its hydrate. When in contact with the water-soluble metal salt of the metal element as the catalytically active component itself, the water-soluble metal salt is usually contacted or mixed with the product obtained in step (3) in a molten state (e.g., heated above its melting point). It is advantageous to mix the water-soluble metal salt with the product obtained in step (3) and then melt it in a closed container. When in contact with an aqueous solution of the water-soluble metal salt of the metal element as the catalytically active component, the water-soluble metal salt of the metal element as the catalytically active component is prepared into an aqueous solution, and then the product obtained in step (3) is impregnated or soaked in the aqueous solution of the water-soluble metal salt, or the aqueous solution of the water-soluble metal salt is sprayed onto the product obtained in step (3). When using an aqueous solution of a water-soluble metal salt as the catalytically active component, there is no particular limitation on its concentration, as long as the metal element as the catalytically active component can be loaded onto the support. Typically, it can be 5-50% by weight, preferably 5-30% by weight. There is also no particular limitation on the temperature of the contact in the form of aqueous solution, which can typically be 20-40°C.
[0035] In step (5), the product obtained in step (4) is calcined to obtain the catalyst. This calcination is typically carried out at 350-650 °C. o The roasting process is carried out at a temperature of 350-500°C, preferably 2-8 hours, preferably 4-8 hours. The roasting atmosphere is usually air or an inert atmosphere.
[0036] In this article, an inert atmosphere refers to an atmosphere that does not participate in chemical reactions under calcination conditions, such as nitrogen or argon.
[0037] The catalyst of this invention is prepared by first heat-treating the support with a weak acid and a strong base, and then loading the catalyst promoter and the catalytic active component. When used to produce aviation kerosene from syngas, the catalyst can break the ASF distribution of the traditional Fischer-Tropsch reaction and obtain high selectivity for aviation kerosene. In addition, acceptable or higher CO conversion rates can also be obtained.
[0038] Therefore, according to another aspect of the present invention, a catalyst prepared by the catalyst preparation method of the present invention is provided. All characteristics of this catalyst are the same as those described above regarding catalyst preparation.
[0039] According to a final aspect of the invention, the use of the catalyst prepared by the method of the invention in the production of aviation kerosene from syngas is provided.
[0040] Before being used in the synthesis of aviation kerosene from syngas, the catalyst of this invention needs to be reduced so that the catalytically active components and optionally present catalyst promoters are in elemental form. For this purpose, the catalyst is typically reduced in a hydrogen-containing atmosphere. The reduction temperature is typically 200-400 °C. o C, preferably 250-350 o C. The reduction pressure is typically 0-4.0 MPa, preferably 0-1.0 MPa (gauge pressure). The reduction time is typically 3-12 h, preferably 6-12 h. Pure hydrogen or a hydrogen-containing mixture can be used as the reduction atmosphere. After reduction, the catalytically active components and catalyst promoters in the catalyst are in elemental form and exhibit catalytic activity.
[0041] In the reaction of producing aviation kerosene from syngas using the catalyst of the present invention, the H2 / CO molar ratio is typically 1-5, preferably 1-3. When this molar ratio is less than 2, the selectivity for aviation kerosene in the reaction can be further improved compared to the case where the molar ratio is greater than or equal to 2. Therefore, in a preferred embodiment of the present invention, the H2 / CO molar ratio is 1 to less than 2. The reaction pressure of the synthesis reaction is typically 1-5 MPa (gauge pressure), preferably 1-3 MPa (gauge pressure). The temperature of the synthesis reaction is typically 150-350°C. o C, preferably 200-300 o C. The W / F (gas hourly space velocity) for this synthesis reaction is typically 5-20 gh mol. -1 8-15 ghmol is preferred. -1 In a preferred embodiment, the reaction pressure in the synthesis of aviation kerosene from syngas is 1-5 MPa (gauge pressure), and the reaction temperature is 150-350 °C. o C, and W / F are 5-20 gh mol -1 In a more preferred embodiment, the reaction pressure in the synthesis of aviation kerosene from syngas is 1-3 MPa (gauge pressure), and the reaction temperature is 200-300 °C. o C and W / F are 8-15 gh mol -1 .
[0042] Compared with existing technologies, the beneficial effects of this invention are as follows: The synthesis of aviation kerosene from syngas is a strongly exothermic reaction that produces water as a byproduct. Cobalt-based monometallic catalysts are prone to oxidation, leading to agglomeration, sintering, and deactivation during the reaction. Conventional Fischer-Tropsch reactions follow an ASF distribution, resulting in low selectivity for the target product (aviation kerosene), theoretically not exceeding 40%. In this invention, by first heat-treating the support with a weak acid and a strong base, and then loading catalytically active components (Ru, Fe, Ni, Co, Pt, Pd, or any combination thereof) and catalytic promoters, a highly dispersed catalyst for syngas-to-aviation kerosene production can be obtained. This addresses the problem of poor catalyst stability during the reaction, improves catalyst stability, and breaks the traditional ASF distribution of the Fischer-Tropsch reaction. In particular, it achieves high selectivity for aviation kerosene and also yields acceptable or higher CO conversion rates.
[0043] Example
[0044] The present invention will be further described below with reference to specific embodiments, but should not be construed as limiting the scope of protection of the present invention.
[0045] Example 1
[0046] Catalyst preparation
[0047] EDTA was dissolved in deionized water to prepare a 0.07 mol / L solution I. 6.7 g of Y-type molecular sieve (Tosoo Corporation, HSZ-320NAA) was weighed and added to solution I, refluxed and stirred for 6 h, filtered, washed with deionized water, and then dried at 120 °C. NaOH was dissolved in deionized water to prepare a 0.4 mol / L solution II. 3.4 g of the previously treated Y-type molecular sieve was added to this solution, and the mixture was heated at 40 °C. o After mixing and stirring at C for 30 min, the mixture was filtered, washed with deionized water, and then dried at 120 °C to obtain precursor a. Manganese nitrate was dissolved in deionized water to prepare a 1 mol / L solution III. 1 g of precursor a was added to solution III, and the mixture was heated at 80 °C. o After being kept at C for 12 hours, the sample was filtered, washed with deionized water, and then dried at 120°C to obtain precursor b. Precursor b was then subjected to air at 650°C. o Calcined at C for 6 hours. Then, 1 g of the obtained product and 1.72 g of cobalt nitrate hexahydrate were weighed and placed in a mortar, and ground for 30 minutes. The resulting product was placed in a sealed glass bottle and incubated at 60°C. o Melt at C for 48 hours. Then melt in a tube furnace under a nitrogen atmosphere at 400°C. o Catalyst A was obtained by calcining C for 4 hours. It contains 15% Co by weight and 10% Mn by weight.
[0048] Catalyst reduction and reaction
[0049] 0.5 g of the obtained catalyst A was loaded into a vertical tubular reactor with a diameter of 9 mm, and catalyst A was arranged in a fixed bed. Hydrogen gas was introduced through the top inlet of the tubular reactor, and catalyst A was continuously reduced for 8 h at a temperature of 400 °C and a gauge pressure of 0 MPa. After the reduction of catalyst A, the temperature was lowered to 250 °C, syngas was introduced, the H2 / CO molar ratio was 1, the reaction pressure was 2 MPa (gauge pressure), and the reaction temperature was 250 °C. o C and W / F are 10 gh mol -1 The reaction proceeded in a continuous sequence. The results are shown in Table 1.
[0050] Example 2
[0051] The preparation of the catalyst in Example 1 was repeated, except that Solution III was replaced with a 1 mol / L aqueous solution of sodium nitrate. The final catalyst B was obtained, which contained 15 wt% Co and 10 wt% Na.
[0052] Catalyst reduction and reaction
[0053] The catalyst reduction and reaction process in Example 1 were repeated, except that catalyst A was replaced with catalyst B. The reaction results are shown in Table 1.
[0054] Example 3
[0055] The preparation of the catalyst in Example 1 was repeated, except that Solution III was replaced with a 1 mol / L aqueous solution of cerium nitrate. The final catalyst C was obtained, which contained 15 wt% Co and 10 wt% Ce.
[0056] Catalyst reduction and reaction
[0057] The catalyst reduction and reaction process in Example 1 were repeated, except that catalyst A was replaced with catalyst C. The reaction results are shown in Table 1.
[0058] Example 4
[0059] The preparation of the catalyst in Example 1 was repeated, except that solution III was replaced with a 1 mol / L aqueous solution of lanthanum nitrate. The final catalyst D was obtained, which contained 15 wt% Co and 10 wt% La.
[0060] Catalyst reduction and reaction
[0061] The catalyst reduction and reaction process in Example 1 were repeated, except that catalyst A was replaced with catalyst D. The reaction results are shown in Table 1.
[0062] Example 5
[0063] The preparation of the catalyst in Example 1 was repeated, except that solution III was replaced with a 1 mol / L aqueous solution of lithium nitrate. The final catalyst E was obtained, which contained 15 wt% Co and 10 wt% Li.
[0064] Catalyst reduction and reaction
[0065] The catalyst reduction and reaction process in Example 1 were repeated, except that catalyst A was replaced with catalyst E. The reaction results are shown in Table 1.
[0066] Example 6
[0067] The preparation of the catalyst in Example 1 was repeated, except that solution III was replaced with a 1 mol / L aqueous solution of potassium nitrate. The final catalyst F was obtained, which contained 15 wt% Co and 10 wt% K.
[0068] Catalyst reduction and reaction
[0069] The catalyst reduction and reaction process in Example 1 were repeated, except that catalyst A was replaced with catalyst F. The reaction results are shown in Table 1.
[0070] Comparative Example 1
[0071] Weigh 1g of Y-type molecular sieve (Tosoo Corporation, HSZ-320NAA) and 1.72g of cobalt nitrate hexahydrate into a mortar and grind for 30 minutes. Place the resulting product in a sealed glass bottle and incubate at 60°C. o Melt at C for 48 hours. Then melt in a tube furnace under a nitrogen atmosphere at 400°C. o C was calcined for 4 hours to obtain catalyst CA, which contained 15% Co by weight in terms of elemental composition.
[0072] Catalyst reduction and reaction
[0073] The catalyst reduction and reaction process in Example 1 were repeated, except that catalyst A was replaced with catalyst CA. The reaction results are shown in Table 1.
[0074] Comparative Example 2
[0075] EDTA was dissolved in deionized water to prepare a 0.07 mol / L solution I. 3.4 g of Y-type molecular sieve (Toso Co., Ltd., HSZ-320NAA) was weighed and added to solution I, refluxed and stirred for 6 h, then filtered. The solution was washed with deionized water and dried at 120 °C to obtain precursor a. Sodium nitrate was dissolved in deionized water to prepare a 1 mol / L solution II. 1 g of precursor a was added to solution II and stirred at 80 °C. oAfter being kept at C for 12 hours, the sample was filtered, washed with deionized water, and then dried at 120°C to obtain precursor b. Precursor b was then subjected to air at 650°C. o Calcined at C for 6 hours. Then, 1 g of the obtained product and 1.72 g of cobalt nitrate hexahydrate were weighed and placed in a mortar, and ground for 30 minutes. The resulting product was placed in a sealed glass bottle and incubated at 60°C. o Melt at C for 48 hours. Then melt in a tube furnace under a nitrogen atmosphere at 400°C. o Calcination with C for 4 hours yielded catalyst CB, which contains 15% Co and 10% Na by weight.
[0076] Catalyst reduction and reaction
[0077] The catalyst reduction and reaction process in Example 1 were repeated, except that catalyst A was replaced with catalyst CB. The reaction results are shown in Table 1.
[0078] Comparative Example 3
[0079] Prepare a 0.4 mol / L solution I using NaOH and deionized water. Weigh 6.7 g of Y-type molecular sieve (Toso Co., Ltd., HSZ-320NAA) and add it to solution I. Incubate at 40°C. o After mixing and stirring at C for 30 min, the mixture was filtered, washed with deionized water, and then dried at 120 °C to obtain precursor a. Sodium nitrate was dissolved in deionized water to prepare a 1 mol / L solution II. 1 g of precursor a was added to solution II, and the mixture was heated at 80 °C. o After being kept at C for 12 hours, the sample was filtered, washed with deionized water, and then dried at 120°C to obtain precursor b. Precursor b was then subjected to air at 650°C. o Calcined at C for 6 hours. Then, 1 g of the obtained product and 1.72 g of cobalt nitrate hexahydrate were weighed and placed in a mortar, and ground for 30 minutes. The resulting product was placed in a sealed glass bottle and incubated at 60°C. o Melt at C for 48 hours. Then melt in a tube furnace under a nitrogen atmosphere at 400°C. o C was calcined for 4 hours to obtain catalyst CC, which contains 15% Co and 10% Na by weight.
[0080] Catalyst reduction and reaction
[0081] The catalyst reduction and reaction process in Example 1 were repeated, except that catalyst A was replaced with catalyst CC. The reaction results are shown in Table 1.
[0082] Comparative Example 4
[0083] 1 g of Y-type molecular sieve (Tosoo Corporation, HSZ-320NAA) was weighed and impregnated with a saturated aqueous solution of 1.72 g of cobalt nitrate hexahydrate, then dried. The sieve was then heated in a tube furnace under a nitrogen atmosphere at 400 °C.o C was calcined for 4 hours to obtain catalyst CD, which contains 15% Co by weight based on elemental composition.
[0084] Catalyst reduction and reaction
[0085] The catalyst reduction and reaction process in Example 1 were repeated, except that catalyst A was replaced with catalyst CD. The reaction results are shown in Table 1.
[0086] Comparative Example 5
[0087] Prepare a 1 mol / L sodium nitrate solution (Synthetic Sodium Nitrate Co., Ltd.) using deionized water. Add 1 g of Y-type molecular sieve (Toso Co., Ltd., HSZ-320NAA) to solution (Synthetic Sodium Nitrate Co., Ltd.) at 80 °C. o The mixture was kept at C for 12 hours, then filtered, washed with deionized water, and dried at 120°C to obtain precursor a. Precursor a was then subjected to 650°C in air. o Calcined at C for 6 hours. Then, 1 g of the obtained product and 1.72 g of cobalt nitrate hexahydrate were weighed and placed in a mortar, and ground for 30 minutes. The resulting product was placed in a sealed glass bottle and incubated at 60°C. o Melt at C for 48 hours. Then melt in a tube furnace under a nitrogen atmosphere at 400°C. o Calcination with C for 4 hours yielded catalyst CE, which contains 15% Co and 10% Na by weight.
[0088] Catalyst reduction and reaction
[0089] The catalyst reduction and reaction process in Example 1 were repeated, except that catalyst A was replaced with catalyst CE. The reaction results are shown in Table 1.
[0090] Table 1
[0091] a: represents the iso / direct ratio of components in aviation kerosene, i.e., the product composition is C8-C. 16 The molar ratio of isomeric hydrocarbons to normal hydrocarbons in hydrocarbons; the higher the iso / normal ratio, the lower the freezing point of the oil, which is more beneficial to the use of aircraft.
Claims
1. A method for preparing a catalyst for producing aviation kerosene from syngas, the catalyst being a supported catalyst comprising a support and a catalytically active component and a catalytic promoter supported on the support, wherein, based on the total weight of the catalyst, the catalyst comprises: (A) One or more elements selected from Ru, Fe, Ni, Co, Pt and Pd, in an elemental composition of 1-50% by weight, are used as the catalytically active component. (B) One or more elements selected from Group I metals, transition elements, and lanthanides of the periodic table, differing from the catalytically active component, and expressed as 1-20% by weight, as a catalytic promoter; (C) Carrier, Its features The catalyst is prepared by a method comprising the following steps: (1) The carrier is ionized using the constant K a 1.0×10 -3 -1.0×10 -1 Heat treatment of weak acid aqueous solution; (2) The carrier obtained in step (1) is heat-treated with an aqueous solution of alkali metal hydroxide under alkaline conditions; (3) The product obtained in step (2) is directly contacted with an aqueous solution of a water-soluble salt of a metal element as a catalyst, or the product obtained in step (2) is filtered, washed, and dried and then contacted with an aqueous solution of a water-soluble salt of a metal element as a catalyst to load the metal element as a catalyst. (4) After filtering, washing, drying and calcining the product obtained in step (3), it is then contacted with the water-soluble metal salt of the metal element as the catalytic active component or its solution to load the metal element as the catalytic active component. as well as (5) The product obtained in step (4) is calcined to obtain the catalyst.
2. The method of claim 1, wherein, based on the total weight of the catalyst, the catalyst comprises: (A) 5-30% by weight, more preferably 12-18% by weight, of the catalytically active component, and (B) 1-15% by weight, more preferably 8-12% by weight, of a catalyst promoter; and (C) 60-94% by weight, more preferably 70-80% by weight of the carrier.
3. The method according to claim 1 or 2, wherein the catalytically active component is one or more elements selected from Ni, Co and Fe, especially Co, Fe or combinations thereof; and / or the catalyst promoter is one or more elements selected from Na, K, La, Ce and Mn, especially La, Ce or combinations thereof; and / or the support is one or more selected from carbon nanotubes, graphene, activated carbon, SiO2, Al2O3, ZrO2, silicon carbide, TiO2 and molecular sieves, preferably one or more molecular sieves, especially Y-type molecular sieves, clinoptilolite, mordenite and ZSM-5, provided that: when the catalyst promoter is Ti, the support is not TiO2, and when the catalyst promoter is Zr, the support is not ZrO2.
4. The method according to any one of claims 1-3, wherein the water-soluble metal salt of the catalytic active component is a nitrate, acetate, chloride salt, their hydrates or any mixture thereof, preferably a nitrate or its hydrate; and / or, the water-soluble salt of the catalytic promoter is a nitrate, acetate, chloride salt, their hydrates or any mixture thereof, preferably a nitrate or its hydrate.
5. The method according to any one of claims 1-4, wherein the weak acid in step (1) is an organic weak acid, preferably selected from one or more of oxalic acid, phenylhexacarboxylic acid, maleic acid, salicylic acid and EDTA, especially EDTA; and / or the concentration of the aqueous solution of the weak acid in step (1) is 0.04-0.5 mol / L, preferably 0.04-0.1 mol / L; and / or the heat treatment in step (1) is carried out under conditions not exceeding the reflux temperature, preferably at 40-100°C. o C. More preferably 70-100 o The process is carried out at a temperature of C; and / or the heat treatment in step (1) is carried out for 1-10 hours, preferably 4-10 hours.
6. The method according to any one of claims 1-5, wherein the alkali metal hydroxide in step (2) is sodium hydroxide, potassium hydroxide, or a combination thereof, preferably sodium hydroxide; and / or, the concentration of the aqueous solution of the alkali metal hydroxide is 0.1-1 mol / L, preferably 0.1-0.5 mol / L; and / or, the heat treatment in step (2) is at 40-100°C. o C. Preferred 40-80 o The heat treatment is carried out at C; and / or the heat treatment time in step (2) is 0.1-2h, preferably 0.1-1h.
7. The method according to any one of claims 1-6, wherein the carrier obtained by step (1) is filtered, washed and dried before the heat treatment in step (2); and / or, in step (3), the product obtained in step (2) is filtered, washed and dried and then contacted with an aqueous solution of a water-soluble salt of a metal element as a catalyst to load the metal element as a catalyst.
8. The method according to any one of claims 1-7, wherein in step (3), the concentration of the aqueous solution of the water-soluble salt of the metal element as a catalyst is 0.1-4 mol / L, preferably 0.5-2 mol / L; and in step (3), the contact between the support and the aqueous solution of the water-soluble salt of the metal element as a catalyst is 40-100 °C. o C, preferably 40-80 o The process is carried out at C; and / or the contact between the support and an aqueous solution of a water-soluble salt of a metal element serving as a catalyst is carried out for 2-24 hours, preferably 4-12 hours.
9. The method according to any one of claims 1-8, wherein in step (4), the water-soluble metal salt of the metal element as the catalytic active component is contacted with the product obtained in step (3) in a molten state, preferably, the water-soluble metal salt of the metal element as the catalytic active component is mixed with the product obtained in step (3) and then melted in a sealed container.
10. The method according to any one of claims 1-9, wherein the drying in steps (2), (3) and (4) is each independently carried out at 60-120°C. o The roasting is carried out under C conditions; and / or, the roasting in steps (4) and (5) is carried out independently at 350-650 °C. o The roasting is carried out at C, preferably at 450-650 °C in step (4). o The roasting in step (5) is carried out at 350-500℃.
11. A catalyst prepared by any one of claims 1-10.
12. Use of the catalyst prepared by any one of claims 1-10 in the production of aviation kerosene from syngas.
13. The use according to claim 12, wherein in the reaction of syngas to aviation kerosene, the H2 / CO molar ratio is 1-5, preferably 1-3, more preferably 1 to less than 2.
14. The use according to claim 12 or 13, wherein in the reaction of syngas to aviation kerosene, the reaction pressure is 1-5 MPa (gauge pressure) and the reaction temperature is 150-350 °C. o C, and W / F are 5-20 gh mol -1 The preferred reaction pressure is 1-3 MPa (gauge pressure), and the preferred reaction temperature is 200-300 °C. o C and W / F are 8-15 gh mol -1 .